The Underpinnings of Ageism: Multiple Mediational Model of Epistemological Style, Social Dominance Orientation, Right-Wing Authoritarianism, and Ageist Attitudes - Richard S. Henry; Paul B. Perrin; Erin R. Smith (Journal of Aging Research)
This study seeks to understand the psychological factors that may contribute to the development and endorsement of ageist belief systems. Dual process theory is used to examine how one’s worldview, beliefs in social hierarchy, authoritarian aggression, authoritarian submission, and conventionalism predict ageist attitudes. Participants living in the United States (n = 407) in 49 states and territories were recruited through this online national study and completed surveys of their ageist beliefs, epistemological style, social dominance orientation (SDO), and right-wing authoritarianism (RWA). RWA, SDO, and naïve realism were all positively associated with ageist beliefs. A hypothesized path model and two alternative models suggested the retention of a model whereby naïve realism led to RWA, which led to SDO, and finally to ageism. All possible direct and indirect effects were significant within the retained model, suggesting the presence of a multiple mediation. The fit of this model was superior to that of models testing alternative theoretical causal chains. Naïve realism may lead to authoritarian aggression, authoritarian submission, and conventionalism, which may then increase the value that people place on social hierarchies, and this may influence the development and retention of ageist beliefs. Helping people to understand what their basic beliefs about the world are and how they may play a role in the development of ageism may assist in reducing ageist attitudes.